Ways of knowing and inclusive management praticices - Feldman, Martha S. et al. (2006)
The authors engage structural and agentic perspectives to examine opportunities for deliberation and the purposeful role of managers in creating those opportunities. Drawing on actor-network theory as a way of understanding the process of structuring knowledge, this essay focuses on the continuous enactment and reenactment of networks of human and nonhuman actants and the associations that connect them. This thinking is applied to policy issues, which the authors propose should be understood as ways of knowing. The fluidity of such ways of knowing provides opportunities for public managers to use the inclusive practices associated with boundary experiences, boundary objects, and boundary organizations to facilitate deliberation. - Reproduced.
Keywords: Public administration; Management